Students' Self-Confidence in Speaking English and Teachers' Professional Identity from Students' Perspective - Suryanto, Bradhiansyah Tri; Imelia, Galuh Rofanda; Fu'adah, Mar'ah Zamratin (Universitas Nurul Jadid, 2025)
English speaking ability is an important skill in foreign language learning, yet many students still show low levels of confidence in speaking, especially in course institutions such as Zain Academy. One of the factors thought to influence students' confidence is their perception of teachers' professional identity, which includes pedagogical competence, interpersonal relationships and affective support. This study aims to find out the relationship between students' perceptions of teachers' professional identity and their level of confidence in speaking English. This study used a quantitative approach with a correlational design. Data were collected through a closed-ended Likert-scale questionnaire administered to 16 Zain Academy students who had attended at least one semester of study. Data were analysed through Pearson correlation test and simple linear regression. The results showed that there was a significant relationship between students' perceptions of teachers' professional identity and their confidence in speaking English, with a correlation value of r = 0.548 and a significance of p = 0.028. The regression test results showed that students' perceptions of teachers' professional identity contributed 30% to the variation in students' self-confidence (R Square = 0.300). This finding supports the theory that perceptions of teacher professionalism play a role in building students' motivation and self-confidence in language learning contexts. The conclusion of this study is that positive perceptions of teachers' professional identity can increase students' confidence in speaking English. Therefore, it is recommended that non-formal education institutions provide training for teachers to develop comprehensive professional qualities, and involve affective and interpersonal aspects to create a learning environment that supports students' courage in communicating.